Bis{S-benzyl 3-[(phenyl)(pyridin-2-yl)methylidene]dithiocarbazato}zinc acetonitrile monosolvate - Ravoof, Thahira B. S. A. (International Union of Crystallography, 2012)
In the title compound, [Zn(C(20)H(16)N(3)S(2))(2)]·CH(3)CN, two different Schiff base moieties coordinate to the central Zn(II) ion as tridentate N,N′,S-chelating ligands, creating a distorted octahedral environment [the smallest angle being 73.24 (6)° and the widest angle being 155.73 (7)°], with the two S atoms in cis positions. The dihedral angle between the mean planes of the two coordinating ligands is 83.65 (5)°. The crystal packing is consolidated by weak C—H⋯N hydrogen-bonding interactions.